Perkembangan Tembakau di Distrik Lampung Masa Kolonial Abad XIX - Syanila Indah; Sonia Ayuning; Yusuf Perdana (Historia Madania: Jurnal Ilmu Sejarah, 2022)
The purpose of this study was to determine the development of tobacco plantations in the Lampung district during the 19th century colonial period and as a source of learning material for the history of plantations in Lampung and local history in Lampung. The method used in this research is using the historical method with several stages, namely heusristic, verification, interpretation and historiography. The results of this study briefly describe the development of tobacco plantations in the Lampung district during the colonial period. And the dynamics of tobacco with many other plantation products can be said to be not easy, the dynamics of tobacco plants that were cultivated during the colonial period experienced many highs and lows of tobacco production. With conditions in the colonial period being in changing weather so that it had an impact on the production of its own tobacco, so that in the 1830s the colonial began to order again for farmers in the Dutch East Indies to plant plantation products that were sold on the international market.